Family Development Session Pendidikan Education and Training in Efforts to Increase Mentoring Capacity for the Social Assistance of the Hope Family Program in Bandung Regency - Rosma Sandratika; Santoso Tri Raharjo; Risna Resnawaty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Family Hope Program (PKH) is a conditional assistance given to someone who is poor and vulnerable to poverty which has an education component, a health component and a social welfare component. The PKH Beneficiary Family (KPM) is accompanied by a social assistant. One form of assistance is the existence of a Family Development Session (FDS) which aims to change the behavior of beneficiary families and encourage KPM to leave PKH. In conducting FDS, social assistants are required to have special knowledge, skills and attitudes so that the implementation of FDS is successful and has an impact as targeted. The knowledge, skills and attitudes of social assistants in this FDS activity are obtained through education and training activities. The purpose of this study is to describe FDS education and training in an effort to increase the capacity of mentoring for PKH social assistants in Bandung Regency. This study uses a descriptive qualitative approach. Data sources come from primary and secondary data sources. Data collection techniques used observation, in-depth interviews, focus group discussions and documentation studies.The results showed that in FDS education and training for PKH social assistants in Bandung Regency